2004
DOI: 10.4025/actascianimsci.v26i4.1719
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and haematological response of Oreochromis niloticus (Osteichthyes: Cichlidae) exposed to single and consecutive stress of capture

Abstract: ABSTRACT. This work is a sequence of studies on tropical fish of economic importance that evaluated the effects of two different stress of handling on the physiology and haematology of Oreochromis niloticus L. acclimated for 10 days before the essay. The stress consisted in net capture of all fish from each aquarium for 30s emersion. Fish exposed to single stress (SS) the samples were collected in the times 0, 10, 20, 30, 40, 50, 60, 120, 180, 240 and 300min. after stress. In the consecutive stress (CS) the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 34 publications
3
27
1
4
Order By: Relevance
“…Handling and sampling stress can ruled out as a causative agent of the variation in leukocyte numbers in the present study. Reduced lymphocyte numbers were described in stressed fishes (Pulsford et al, 1994;Martins et al, 2004) however, as opposed to our results, these authors observed an increase in neutrophils and leukocyte numbers. In fact, the contradictory results regarding neutrophil and leukocyte numbers occurs because the response depends on fish species, stress intensity, duration (Pickering et al, 1982;TavaresDias et al, 2001), nutritional condition (Pickering et al, 1982) and stressor (Davis & Schreck, 1997).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Handling and sampling stress can ruled out as a causative agent of the variation in leukocyte numbers in the present study. Reduced lymphocyte numbers were described in stressed fishes (Pulsford et al, 1994;Martins et al, 2004) however, as opposed to our results, these authors observed an increase in neutrophils and leukocyte numbers. In fact, the contradictory results regarding neutrophil and leukocyte numbers occurs because the response depends on fish species, stress intensity, duration (Pickering et al, 1982;TavaresDias et al, 2001), nutritional condition (Pickering et al, 1982) and stressor (Davis & Schreck, 1997).…”
Section: Discussioncontrasting
confidence: 56%
“…Elevated plasmatic glucose was also observed after stress capture in pacu (Abreu et al, 2009), rainbow-trout (Wells & Pankhurst, 1999), Nile tilapia (Martins et al, 2004), goldfish C. auratus (Dror et al, 2006), sablefish Anoploma fimbria (Lupes et al, 2006). Fish (L. rohita) fed glucan supplemented diets and submitted to consecutive blood sampling, as well as the same in the present experiment did not show any differences in blood glucose concentration during trial (Misra et al, 2006a(Misra et al, , 2006b) and this results are attributed to adequate managing during sampling and biometrics and not to prebiotic supplementation.…”
Section: Discussionmentioning
confidence: 97%
“…The first portion was collected with anticoagulant 10 % EDTA (ethylenediaminetetraacetate) to measure hematocrit (Ht), hemoglobin (Hb) and white blood cells (WBCs). Ht was determined as described by Reitman and Frankel (1957), hemoglobin (Hb) was determined by the hemoglobin kits which is a standardized procedure of the cyanomet hemoglobin method as well as the total count of white blood cells (WBCs) was carried out by the indirect method (Martins et al 2004). The second portion of the blood sample was allowed to clot overnight at 4°C, centrifuged at 3,000 rpm for 10 min.…”
Section: Growth Performance and Feed Utilization Indicesmentioning
confidence: 99%
“…Blood smears in duplicate were stained with a lood combination of Giemsa/May-Grünwald (Rosenfeld, 1947). The smears were used for differential leukocyte count and the total count of thrombocytes and leukocytes (Martins et al, 2004).…”
Section: Hematological Parametersmentioning
confidence: 99%
“…In fish, carrageenin, thioglycolate and inactivated Aeromonas hydrophila were tested in the swim bladder of Piaractus mesopotamicus (Martins et al, 2000;Moraes et al, 2003;Bozzo et al, 2007) and Oreochromis niloticus (Martins et al, 2004;Dotta et al, 2011). According to Bozzo et al (2007), thioglycolate and inactivated Aeromonas hydrophila induced vascular congestion, accumulation of thrombocytes followed by macrophages, granulocytes and oedema.…”
Section: Introductionmentioning
confidence: 99%